PEMERTAHANAN IDENTITAS BUDAYA KARO DALAM PAGELARAN SINABUNG ART FESTIVAL (SAF) DI DESA KUTA GUGUNG KABANJAHE TANAH KARO - Anton Sitepu; Karisma Erikson Tarigan (Smart Education, 2023)
Abstract: Festivals have a strong function in building communication and introducing culture. The purpose of this community service is to describe the role of the Sinabung Art Festival (SAF) in building a karo cultural identity, especially for people from different cultural backgrounds. In this community service, the form of activity is carried out using observation and questionnaires. From the results of the data obtained, there were 8 (eight) tribes who attended the Sibanung Art Festival (SAF) activities. From visitor data, it was obtained that 38% were Batak Toba, 24% were Karo, 18% were Javanese, 7% were Nias and Chinese, and 2% were Pakpak, Madura and Mandailing tribes. From this activity it can be seen that not only the sons and daughters of the Karo area are interested in this festival but there are also several tribes involved in it.Keywords: culture; sinabung festival; the karo tribeAbstrak: Festival mempunyai fungsi yang kuat dalam membangun komunikasi dan memperkenalkan budaya. Adapun tujuan pengabdian ini adalah mendeskripsikan peranan Sinabung Art Festival (SAF) dalam membangun identitas budaya karo, terutama bagi masyarakat dari latar belakang budaya yang berbeda. Pada pengabdian masyarakat ini, bentuk kegiatan yang dilakukan menggunakan metode observasi, wawancara dan angket. Dari hasil data yang deperoleh terdapat 8 (delapan) suku yang menghadiri kegiatan Sibanung Art Festival (SAF) dari data pengunjung yang diperoleh bahwa 38% suku Batak Toba, 24% Suku Karo, 18% suku Jawa, 7% suku Nias dan Cina, dan 2% suku Pakpak, madura, dan suku mandailing. Dari kegiatan ini terlihat tidak hanya putra putri derah karo yang meminati festival ini tetapi ada beberapa suku juga yang terlibat didalamnya.Kata kunci: budaya; sinabung festival; suku karo